Alterations in the α2δ ligand, thrombospondin‐1, in a rat model of spontaneous absence epilepsy and in patients with idiopathic/genetic generalized epilepsies. (15th September 2017) - Santolini, Ines; Celli, Roberta; Cannella, Milena; Imbriglio, Tiziana; Guiducci, Michela; Parisi, Pasquale; Schubert, Julian; Iacomino, Michele; Zara, Federico; Lerche, Holger; ,; ,; et al.
Summary: Objectives: Thrombospondins, which are known to interact with the α2 δ subunit of voltage‐sensitive calcium channels to stimulate the formation of excitatory synapses, have recently been implicated in the process of epileptogenesis. No studies have been so far performed on thrombospondins in models of absence epilepsy. We examined whether expression of the gene encoding for thrombospondin‐1 was altered in the brain of WAG/Rij rats, which model absence epilepsy in humans. In addition, we examined the frequency of genetic variants of THBS1 in a large cohort of children affected by idiopathic/genetic generalized epilepsies (IGE/GGEs). Methods: We measured the transcripts of thrombospondin‐1 and α2 δ subunit, and protein levels of α2 δ, Rab3A, and the vesicular glutamate transporter, VGLUT1, in the somatosensory cortex and ventrobasal thalamus of presymptomatic and symptomatic WAG/Rij rats and in two control strains by real‐time polymerase chain reaction (PCR) and immunoblotting. We examined the genetic variants of THBS1 and CACNA2D1 in two independent cohorts of patients affected by IGE/GGE recruited through the Genetic Commission of the Italian League Against Epilepsy (LICE) and the EuroEPINOMICS‐CoGIE Consortium. Results: Thrombospondin‐1 messenger RNA (mRNA) levels were largely reduced in the ventrobasal thalamus of both presymptomatic and symptomatic WAG/Rij rats, whereas levels in the somatosensory cortex were unchanged. VGLUT1 protein levels were also reduced in the ventrobasal thalamus of WAG/Rij rats. Genetic variants of THBS1 were significantly more frequent in patients affected by IGE/GGE than in nonepileptic controls, whereas the frequency of CACNA2D1 was unchanged. Significance: These findings suggest that thrombospondin‐1 may have a role in the pathogenesis of IGE/GGEs.